”Kvinnohat eller Trolldom?” : En jämförande studie om häxprocessen och nåjder i Sverige. - Petersson, Daniel (Linnéuniversitetet, Institutionen för kulturvetenskaper (KV), 2023)
As the era of Christianity is taking a firm foothold of Europe and Scandinavia during the late 1500s and early 1600s. The prosecution, accusations, and pure terror against anyone who did not fit the mold of a true Christian was faced with doubt, suspicion, and allegations of being in a pact with the Devil. Even if Christianity was becoming the main religion in the regions. It was common among townsfolk when in great doubt, sickness and worries to pay a visit to the old lady, the shaman, or the local healer. Some of these shamans depending on where you lived could also be a part of the Indigenous people of Scandinavia, the Sami. Whether you where that local old lady, that local shaman or one of the many regional Sami’s roaming the north of Scandinavia during this period of history, it was extremely dangerous to express local beliefs, superstitions, and an alternative faith then Christianity. The goal of this essay is to take a closer look at some of these cases, analyze the trials and prosecutions of these witches and Sami Shamans within Swedish courts, to see the similarities and discuss six cases in greater details. The conclusion of this essay is that we see some similarities between Swedish witches and Sami people who used magic, however the use and/or blame off alcohol may vary, the methods on how these witches would inflict “hurtful magic” was different and so too the trials. There is a “clearer mentioning” of torture on “Swedish witches” then Sami witches. The Swedish witches would use “totems” and items to cast spells, while Sami witches would use vocal incantations to hurt their victims.